AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2025 - Thill, Marc; Janni, Wolfgang; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bartsch, Rupert; Bauerfeind, Ingo; Bjelic-Radisic, Vesna; Blohmer, Jens; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva Maria; et al. (Breast Care, 2025)
The Breast Committee of the Arbeitsgemeinschaft Gyn kologische Onkologie (AGO; German Gynecological Oncology Group) presents the 2025 update of the evidence-based recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer (mBC).
CRIS-Team Scopus Importer:2025-05-16
Keywords: AGO; Diagnosis; Metastatic breast cancer; Recommendations; Treatment